2021
DOI: 10.1097/wnp.0000000000000877
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG as a Prognostic Tool in Suspected Anti-N-Methyl-d-Aspartate Receptor Antibody Encephalitis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In anti-NMDAR encephalitis, a significant increase in δ relative band power and a significant decrease in β relative band power and β absolute band power in the posterior region have been reported ( 33 ). A higher peak frequency within the delta range was associated with poorer clinical outcomes in anti-NMDAR encephalitis ( 34 ). It is widely known that almost all recorded neurons spontaneously oscillate slowly in the delta range when they are anatomically or functionally disconnected from other cortical regions ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In anti-NMDAR encephalitis, a significant increase in δ relative band power and a significant decrease in β relative band power and β absolute band power in the posterior region have been reported ( 33 ). A higher peak frequency within the delta range was associated with poorer clinical outcomes in anti-NMDAR encephalitis ( 34 ). It is widely known that almost all recorded neurons spontaneously oscillate slowly in the delta range when they are anatomically or functionally disconnected from other cortical regions ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the anti-NMDARE, the enhanced delta power in the NMDA-receptor antibodies positive model across a wide range of time-constant fluctuations has also been reported ( 36 ), while the weaker delta power thereby indicates a recovery in patients with encephalitis ( 37 ). Additionally, a higher delta peak is found to be associated with poorer clinical outcomes and thus indicates anti-NMDAR-mediated synaptic dysfunction ( 38 ). Considering theta activity is regarded as a credible EEG indicator of normal brain functions including attention and memory ( 39 ), and delta activity is involved in the integration of cerebral activity with homeostatic processes ( 40 ), the distortions of both rhythmic powers may thereby implicate the persistent and residual pathological states such as anhedonia or reward deficiency ( 40 ) in anti-NMDARE patients even after clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Its performance in Chinese patients was subsequently evaluated in a multicenter, prospective study by Peng et al It showed good discrimination and calibration power with an AUC of 0.86 and a Pearson correlation coefficient of 0.53 (6). On the contrary, results from another study showed that the NEOS score was not associated with one-year outcomes of patients (13). However, this study only included a small sample size (20 patients) which may lead to substantial statistical bias.…”
Section: Discussionmentioning
confidence: 99%